Atrial Fibrillation, Heart Failure Phenotypes, and Mortality Risk in the Nationwide START Registry: A Propensity Score Matching Analysis - Danilo Menichelli; Emilia Antonucci; Gianluca Gazzaniga; Daniela Poli; Giuseppe Armentaro; Giordano di Carlo; Rossella Marcucci; Paolo Calabrò; Arturo Cesaro; Gualtiero Palareti; Angela Sciacqua; Pasquale Pignatelli; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2025)
Background Data on atrial fibrillation (AF) and heart failure (HF) with preserved ejection fraction (HFpEF) are scarce. We investigated the association of HFpEF with all‐cause mortality in AF. Methods We included 10 369 patients with AF on oral anticoagulants from the nationwide ongoing START (Survey on Anticoagulated Patients Register) registry. Patients were divided into 3 groups: (1) no HF, (2) HF with reduced EF/HF with mildly reduced EF (EF ≤50%), and HFpEF (EF >50%). Patients with HF should have had a clinical diagnosis or a history of HF hospitalization. The association between HF types and all‐cause mortality was investigated by Cox proportional hazards regression analysis to estimate hazard ratio (HR) and 95% CI for each factor. The Fine–Gray model and propensity score matching were used. Results Mean age was 76.4±9.4 years and 45.8% were women. Overall, 2309 (22.2%) patients had HF, of whom 47.4% had HFpEF. During 720±576 days of follow‐up (20 747 patients/year), 727 deaths occurred (3.5 per 100 patient‐years). After propensity score matching, both HF with mildly reduced EF/HF with reduced EF and HFpEF were associated with all‐cause mortality (HR, 1.33; P=0.037 and HR, 1.49; P=0.004). HFpEF was associated with mortality in men (HR, 1.654; P=0.001) but not in women (HR, 1.243; P=0.175). In HFpEF, age≥75 years (HR, 2.247; P=0.003), chronic respiratory disease (HR, 2.109; P<0.001), anemia (HR, 1.482; P=0.035), paroxysmal AF (HR, 0.528; P=0.012), creatinine clearance<30 mL/min (HR, 1.791; P=0.018), direct oral anticoagulants (HR, 0.575; P=0.005), and renin‐angiotensin inhibitors (HR, 0.670; P=0.033) were associated with all‐cause mortality. Conclusions HFpEF is frequent in patients with AF and associated with an increased mortality, especially in men. Comorbidities and treatments associated differently with mortality according to HF phenotype. Registration URL: https://www.clinicaltrials.gov; Unique identifier: NCT02219984.